Planning Product Promotion and Marketing Strategies through Social Media for Ahong Grocery Stores - Shieny Tan Putri; Hesnitati Hesnitati (Universitas Internasional Batam, 2023)
Ahong Grocery store is an MSME that is engaged in selling products that are basic needs of the community such as rice, flour, sugar, spices, cooking spices, eggs, cooking oil, and others. Since running the business, Ahong Grocery Store has continued to experience an increase in revenue every year. But even so, Mr. Ahong as the owner of the business admits that the net income earned is only enough to finance operational activities, home loans and daily needs, so he hopes that there are ways to increase business income. In this practical work, planning and implementing promotional and marketing strategies to sell products are carried out by utilizing social media as a promotional platform in order to increase business sales and increase income. Data collection was carried out by interviewing the owner of the store, and the data obtained is primary data in the form of partners' monthly sales income for the period 2010-2021 along with the products and prices of the products sold. The data analysis method is carried out quantitatively by analyzing partners' sales income data in the form of numerical figures and analyzing the increase in business income during the promotion implementation period. The method of analysis was also carried out qualitatively by interpreting the relationship between increased income and the promotion strategy implemented. The result of the practical work is that the partner's monthly income has increased by 17% since the implementation of the promotional strategy on social media, and the partner's Instagram accounts have managed to garner a total amount of 252 followers. Based on the results of practical work, it is recommended that partners continue to plan promotional strategies and implement them because it is proven that promotions through social media can increase business sales and income.